Conhecimento e magia : o Fausto de Marlowe - Marchi, Cláudia de (2022)
Christopher Marlowe's tragic story of Doctor Faust brings modernity to life with a myth that goes beyond generations: a man who, eager for knowledge, dissatisfied with Christian dictates, unresigned by his human limitations, decides to embark on the paths of natural magic, in this case , of necromancy, to negotiate with the devil and, in exchange for his soul, live twenty-four years full of wisdom and pleasures. Faust breaks with the fear of the satanic figure spread by Protestant reformers and calls Mephistopheles to negotiate with him, revealing his hedonistic yearnings and religious questions that, for the 16th century, are in tune with atheism. Marlowe, an outsider in his time, is reflected in his character and ends his text confirming Epicurus' paradox about the inexistence of a God who is, at the same time, omnipresent, omnipotent and benevolent. In the pages of the Marlowean text, a myth of modernity and the atheism of his time appears.